IMPLEMENTASI METODE CERTAINTY FACTOR PADA SISTEM PAKAR PENDETEKSI KERUSAKAN PRINTER - Putu Bagus Adidyana Anugrah Putra (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
The printer is an essential requirement in supporting the daily activities of several business fields, namely printing, design, office, and others. Damage to the printer needs proper handling and right so that if not handled immediately will be detrimental to the user. The design of this system uses the Waterfall software development method which consists of five stages, namely requirements definition (feature determination stage), system and software design includes two activities, namely analysis (Data Flow Diagram and Entity Relationship Diagram) (table design, navigation design using a sitemap and interface), implementation and unit testing (realize and test the design results), integration and system testing and operation and maintenance (maintenance). The system was tested with Blackbox testing, which resulted in the system's functionality running well. The calculation process using the Certainty Factor will produce damage experienced and the solution